Implementation Of The Atik Model In Developing Kinesthetic Intelligence By Mimicking Pattern Movements At Tkq Nurul Huda - Novasari, Novasari; Luthfiah, Eva; Fauziah, Anggun; Lastari, Deta; Watini, Sri (Universitas Muhammadiyah Ponorogo, 2024)
Multiple Intelligences, often referred to as multiple intelligences, emphasize the ability to solve problems and create works of art. One of these intelligences is kinesthetic intelligence. Kinesthetic intelligence refers to the ability to use all parts of the body through movement to express thoughts and feelings. However, children's abilities vary, and not all children possess strong kinesthetic intelligence, as observed at TKQ Nurul Huda. This research aims to determine the importance of developing kinesthetic intelligence through imitating movements based on pattern concepts using the ATIK model, which focuses on image patterns. The research method used is Classroom Action Research (CAR), with data collection techniques involving student observation and documentation. The results show that the implementation of the ATIK model in imitating movements according to picture patterns revealed that 68.25% of children developed as expected (BSH), while 31.25% developed very well (BSB). Therefore, it can be concluded that the implementation of the ATIK model effectively develops kinesthetic intelligence in kindergarten children and enhances their imagination.